Alternative modes of client binding enable functional plasticity of Hsp70: letter - Mashaghi Tabari, Alireza; Bezrukavnikov, Sergey; Minde, David P.; Wentink, Anne; Kityk, Roman; Zachmann-Brand, Beate; Mayer, Matthias P.; Kramer, Günter; Bukau, Bernd; Tans, Sander J. (Nature, 2016)
Hsp70 binds unfolded protein segments in its groove, but can also bind and stabilize folded protein structures, owing to its moveable lid, with ATP hydrolysis and co-chaperones allowing control of these contrasting effects.